2015
DOI: 10.1080/15226514.2015.1086303
|View full text |Cite
|
Sign up to set email alerts
|

Potatoes – A crop resistant against input of heavy metals from the metallicaly contaminated soil

Abstract: The objective of our study was to assess the extent of accumulation of cadmium, lead and zinc in potato tubers depending on the concentration of these heavy metals in soil and to evaluate the resistance of 11 cultivars of potato cultivated in 5 localities of the Slovakia against input of these heavy metals into the consumption part of potato. Contents of Cd (Pb, Zn) in soil were 0.94-2.54 (18.03-24.90, 35.71-72.40) mg/kg in soil extract by aqua regia and 0.030-0.188 (0.149-0.356, 0.052-0.238) mg/kg in soil ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…This finding agrees with results reported by Braun et al (2011), Hadi et al (2014 as well as Roma et al (2017). Farmyard manure and undersown catch crops contributed to increase the iron content in potato tubers due to the fact that the biomass of both farmyard manure and green manures incorporated into the soil was an additional source of macro-and microelements available for the plants (Musilova et al, 2016;Garrido et al, 2017). Tubers produced under organic farming system following green manures and farmyard manure application contained higher iron content compared to potato tubers produced under integrated production system.…”
Section: Iron Contentsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding agrees with results reported by Braun et al (2011), Hadi et al (2014 as well as Roma et al (2017). Farmyard manure and undersown catch crops contributed to increase the iron content in potato tubers due to the fact that the biomass of both farmyard manure and green manures incorporated into the soil was an additional source of macro-and microelements available for the plants (Musilova et al, 2016;Garrido et al, 2017). Tubers produced under organic farming system following green manures and farmyard manure application contained higher iron content compared to potato tubers produced under integrated production system.…”
Section: Iron Contentsupporting
confidence: 92%
“…Potato tubers provide valuable micronutrients necessary for human nutrition (Snapp et al, 2005;Musilova et al, 2016;Roma et al, 2017). In the present research, the higher copper content was recorded in the tubers of potato tubers issued from control plots where only mineral fertilisers were applied.…”
Section: Copper Contentsupporting
confidence: 49%
“…In the remaining plots manured with undersown catch crops, the potato tuber content of copper differed insignificantly from the concentration of this micronutrient in farmyard manure-amended units. In the research by Musilova et al ( 2016 ) and Garrido et al ( 2017 ), the authors have demonstrated that manuring of potato with vermicompost and green manures contributes to a decline in the potato tuber content of copper. In the study reported here, production system affected the copper content in potato tubers.…”
Section: Resultsmentioning
confidence: 99%
“…A blank sample was treated in the same way. The digested substances were subsequently filtered through a quantitative filter paper Filtrak 390 (Munktell, Germany) and filled with deionized water to a volume of 100 mL [34].…”
Section: Chemicals and Equipmentmentioning
confidence: 99%
“…The same way was used for blank sample preparation. After filtration (Filtrak 390; Munktell, Germany) of digested substances deionized water was added to a volume of 50 mL [34,35]. The contents of heavy metals were determined using AAS (atomic absorption spectrometry) method: Cd, Pb: GF-AAS, and Ni F-AAS.…”
Section: Plant Samplesmentioning
confidence: 99%